2020
DOI: 10.1016/j.ymssp.2019.106516
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations and experimental measurements on the structural dynamic behaviour of quasi-periodic meta-materials

Abstract: The periodic structures have various applications in vibroacoustic engineering fields since they introduce frequency band effects due to the periodic discontinuities in the geometrical or material configurations: this can lead to increased performances. This paper is focused on the analysis of quasi-periodic structures: instead of using strictly repeated patterns, a certain degree of irregularity is introduced. Quasi-periodic lattices are defined as assemblies of two different elements in two directions. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In recent years, the emerging metamaterials based on local resonators provide new ways to deal with low-frequency vibration and noise issues [1][2][3][4][5][6]. Metamaterials present sub-wavelength bandgaps (at frequencies much lower than the first Bragg bandgap), within which wave propagation is prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the emerging metamaterials based on local resonators provide new ways to deal with low-frequency vibration and noise issues [1][2][3][4][5][6]. Metamaterials present sub-wavelength bandgaps (at frequencies much lower than the first Bragg bandgap), within which wave propagation is prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that this approach can be extended to 2 D quasi-periodic pattern using the Thue-Morse morphism sequence. 15…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, long-range periodicity can be broken in a controlled way using the concept of quasicrystals [17][18][19]. Examples are known in * bart.vandamme@empa.ch one, two, or three dimensions, e.g., Fibonacci sequences [20], modulation of a periodic sequence [15,21,22], or certain tessellations [23]. Quasicrystals exhibit no translational periodicity, but they contain local symmetries interacting with impinging wave fields [24].…”
Section: Introductionmentioning
confidence: 99%